Kajian Pantangan Konsumsi Sayuran Hijau, Pola Makan dan Status Gizi Masyarakat Adat di Desa Detuara Kabupaten Ende - Febronia Pricilia Woi; Anna Henny Talahatu; Marselinus Laga Nur (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Food taboos in Indonesia are still a problem because there are still many foods that should be consumed but are still taboo. As a result, pregnant women, nursing mothers, infants and children dare not consume certain foods, reducing their food intake, which can reduce their nutritional status. The indigenous people in Detuara Village have a taboo of not consuming green vegetables during a traditional ritual called Pire Kema One in the process of building a house. This study aims to examine the practice of abstinence from green vegetable consumption, diet, and nutritional status of indigenous people in Detuara Village. This type of research is qualitative research using phenomenological methods with in-depth interviews and SQ-FFQ to assess food consumption habits with data obtained in the form of adequate levels of energy, protein, fat and carbohydrates. The informants consisted of four main informants and four key informants. The informants were selected using purposeful sampling. The results showed that all informants complied with the abstinence from consuming green vegetables until the house construction process was completed. Four informants (100%) had a poor diet during the abstinence from green vegetable consumption, while only one informant (25%) had a good diet during the normal diet. There were two informants (50%) who had normal nutritional status. There was one informant (25%) with overweigth nutritional status and one informant (25%) with obese nutritional status. Conclusion Food taboos still apply in Detuara Village until now and there will be bad risks if you violate these taboos.